Patch Management in OT Environment - Seppänen, Tanja Elisabet (2024)
Critical and industrial infrastructure systems have previously been isolated to a great degree but due to the increased need for e.g. remote access and data collection, the industrial systems have become more connected, and thereby, exposed to more cyber threats. This research is focused on operational technology (OT) security and particularly on patch management in OT environment. The research question is formed around the implementation of patch management in a way that minimizes cyber risks and production disruptions. Patches are an efficient method to protect OT environment, but the patch deployment often requires production disruption. The OT systems set requirements for high availability and safety which make patch management planning more complex than in normal IT systems. Furthermore, the lifecycle of an OT system is usually longer and not all OT systems can necessarily be patched. The research method in this thesis is Design Science Research Methodology that is used to create an artifact. The artifact is a checklist for systematic patch management in OT environment. The findings are collected via semi-structured interviews with IT and OT professionals. In addition to the inter-views, the artifact is further developed in a small-scale workshop with the security professionals. The findings of this thesis suggest that the OT patch management is de-pendent on technology, people, and processes. Communication and collaboration between the IT & OT professionals and the relevant stakeholders has the most remarkable impact on patch management and minimization of cyber risks and production disruptions. Other remarkable factors are OT asset management, patch automation, backups and rollback, lifecycle management, manual patching, allocation of sufficient resources, and regular maintenance. The demonstration and evaluation of the artifact is limited to three production sites of a case study company. Future research in other organizations or industries could support the further development of the artifact.